2016
DOI: 10.15835/nbha44210572
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and Molecular Analysis of the Three Arbutus Species of Greece

Abstract: Arbutus andrachne, A. unedo and A. × andrachnoides found in the Greek macchia are promising species for reforestations, ornamental use, as well as for medicinal use and the food industry. Μorphological traits and molecular markers (RAPD) were used to identify and distinguish these Arbutus species to facilitate their exploitation. Since there are no descriptors established for Arbutus spp., 23 qualitative morphological characteristics of crown, foliage, bark, flowering, fruiting, and four quantitative morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
0
4
1
Order By: Relevance
“…× andrachnoides, were genetically more similar to A. andrachne than to A. unedo. Between the two populations of A. andrachne, from Kalamos and Varympompi, no groupings were observed as in the present work, probably due to the small distance in which the plants were located [24]. In a study carried out on the related species A. unedo originating from nine countries using nine AFLP markers, two populations originating from Greece (specifically from Athens and Sithonia), it was found that the populations have a genetic uniformity among them, and they could be distinguished from the Atlantic and Mediterranean groups [26].…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…× andrachnoides, were genetically more similar to A. andrachne than to A. unedo. Between the two populations of A. andrachne, from Kalamos and Varympompi, no groupings were observed as in the present work, probably due to the small distance in which the plants were located [24]. In a study carried out on the related species A. unedo originating from nine countries using nine AFLP markers, two populations originating from Greece (specifically from Athens and Sithonia), it was found that the populations have a genetic uniformity among them, and they could be distinguished from the Atlantic and Mediterranean groups [26].…”
Section: Discussioncontrasting
confidence: 80%
“…Since it is the first time that remote populations of A. andrachne have been genetically studied using molecular markers, no comparison can be made with other works. In another paper by Bertsouklis and Papafotiou [24], two populations of A. andrachne were studied, but they grow naturally close among them (Kalamos and Varympompi, distance about 12 km). In this paper, the relationship among species A. andrachne, A. unedo, and their natural hybrid A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strawberry tree studies using genomic tools, particularly DNA markers techniques, are relatively scarce and generally use randomly amplified markers: RAPD, ISSR, and AFLP, to assess the genetic variability and population structure of the species at the regional level [ 17 , 18 , 19 ] or covering its whole geographic range [ 20 ], or for discrimination from related species [ 21 ]. In one of these studies [ 19 ], cross-species SSR markers developed for Vaccinium spp.…”
Section: Introductionmentioning
confidence: 99%